SYNTHESIS OF MgO NANOPARTICLES AND THEIR INCORPORATION INTO TiO2 SENSIBILIZED SOLAR CELLS - Rojas, O. (2017)
Nanoestructured TiO2 solar cells modified with MgO (TiO2-MgO) were assembled and characterized; they were sensitized with N791 dye. The MgO modification of the TiO2 films was performed using suspensions with different concentrations of Mg(OH)2 prepared from magnesium nitrate in aqueous solution. One drop of the suspension was placed on top of the film and then was sintered at 530 °C during 30 min. Unsealed cells and sealed cells were obtained, the latter achieved an efficiency of 4.4%, representing an increase of 69% compared to the unmodified sealed cells, which showed an efficiency of 2.6%. Solar efficiency measurements were also performed in darkness and under illumination. It was found that the efficiency diminished 19% in darkness after 22 days, but under illumination diminished 76 % in two days.